Analisis Penghasilan Monetisasi Google AdSense Pada Website Prakata.Id Dalam Perspektif Ekonomi Syariah - Supriyadi, Yodi; Jalaludin, Jalaludin; Nurhayati, Rina (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
The migration of mass media to the internet has made many digital advertising companies appear, one of which is Google AdSense as the largest advertising company opening advertising services. Prakata.id is one of the websites that has collaborated with Google AdSense, indexed by search engines, and is a source of website income. The purpose of this research is to find out the mechanism of cooperation and monetisation of Google AdSense with the Prakata.id website and to find out the monetisation income of Google AdSense on the Prakata.id Website from a sharia economic perspective. The method used in this research is descriptive qualitative method, primary data sources obtained from interviews and observations about Google AdSense monetisation on the website to the editorial board of the Prakata.id Website, National Press Journalists, Members of the Purwakarta Online Journalists Association, Legal observers. Data analysis techniques use data reduction, data display, and data verification. The conclusion of this research is that the cooperation between Prakata.id Website and Google AdSense starts from the publisher of Prakata.id website providing ad slots, ad serving by Google AdSense, and getting monetisation results. Furthermore, the income from Google AdSense monetisation cooperation on the Prakata.id Website is not yet in accordance with Islamic economics. Because policies related to unique content are still unclear and there are no indicators that show which parts of website content Google considers not in accordance with AdSense policies. In addition, publishers do not have the right to propose profit sharing if there is an excess of achieving the viewer target. The type of shirkah in Google AdSense monetisation cooperation with Prakata.id Website is syrikah abdan, with Google AdSense capital as a digital advertising service provider, while Prakata.id Website as a publisher or publisher of advertisements.